THE INFLUENCE OF CUSTOMER RELATIONSHIP MANAGEMENT AND SERVICE QUALITY ON COMPANY IMAGE AND CUSTOMER LOYALTY IN PT BANK TABUNGAN PENSIUNAN NASIONAL TBK BANJARMASIN BRANCH OFFICE - Doddy Setiawan; Lilik Setiawan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research aims to find out and analyze the influence among customer relationship management and service quality on corporate image, as well as the influence of customer relationship management, service quality and corporate image on customer loyalty at PT. Bank Tabungan Pensiunan Nasional, Tbk Branch Banjarmasin. This research method uses explanatory research. The population is current account customers, time deposit customers, and savings customers with a sample size of 102 respondents. The sampling technique used purposive sampling with data analysis using structural equation modeling (SEM) with AMOS21 application. The results showed that there is an effect of customer relationship management and service quality on corporate image. There is an effect of customer relationship management, service quality and company image on customer loyalty, customer relationship management provides a greater influence on customer loyalty without going through the corporate image, service quality carried out through a good corporate image will have a greater influence on customer loyalty at PT. National Pension Savings Bank, Tbk Branch Banjarmasin.